ENVIRONENTAL COMPONENT MANAGEMENT AND ENVIRONMENTAL POLLUTION PROBLEMS - Karimov Abduvoxid,; Tobirov Odiljon, (TADQIQOTLAR, 2025)
Abstract: Environmental pollution has become one of the most pressing global challenges, posing serious threats to human health, ecosystem stability, and sustainable development.  This  article  provides  a  comprehensive  review  of  environmental component management (ECM) as an integrated approach to addressing environmental pollution problems. The study examines the interactions between key environmental components—air,  water,  soil,  and  biological  systems—and  the  impacts  of anthropogenic activities on their degradation. Various types of pollution, including air, water, soil, chemical, and plastic pollution, are analyzed with reference to their sources, consequences,  and  global  significance.  The  article  also  discusses  management strategies such as green infrastructure, waste reduction, regulatory frameworks, and technological  innovations,  including  bioremediation,  nanotechnology,  and  digital monitoring  systems.  Case  studies  from  different  regions  highlight  successful management practices and policy implementations aimed at reducing environmental risks. The findings emphasize that effective environmental component management requires an interdisciplinary, technology-driven, and policy-supported framework to mitigate pollution and enhance ecological resilience. The study concludes by outlining future directions for environmental management focused on innovation, stakeholder collaboration, and sustainable governance.